2011
DOI: 10.1002/ajmg.a.34046
|View full text |Cite
|
Sign up to set email alerts
|

Associated anomalies among infants with oral clefts at birth and during a 1‐year follow‐up

Abstract: Reports of birth defects rates may focus on defects observed in the newborn period or include defects diagnosed at older ages. However, little information is available on the rates of additional anomalies detected after birth or on the ages at which such anomalies are diagnosed. The aims of this work were to describe the initial diagnoses of oral clefts, isolated or associated with other defects, in newborn infants ascertained in hospitals of the ECLAMC network, and diagnostic changes that occurred due to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
3
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 36 publications
11
72
3
9
Order By: Relevance
“…When compared to literature (0-13.3 %), higher percentage of chromosomal aberrations found in isolated clefts in our pool (44 %) can be explained by the age of the embryos and fetuses -usually between day 43 and week 12 (20,23). It is nearly impossible to diagnose some associated congenital defects at such an early age.…”
Section: Discussioncontrasting
confidence: 62%
“…When compared to literature (0-13.3 %), higher percentage of chromosomal aberrations found in isolated clefts in our pool (44 %) can be explained by the age of the embryos and fetuses -usually between day 43 and week 12 (20,23). It is nearly impossible to diagnose some associated congenital defects at such an early age.…”
Section: Discussioncontrasting
confidence: 62%
“…2,3 Approximately 65% to 70% of cleft lip with or without cleft palate (CLP) and 40% to 70% of cleft palate only (CP) were isolated defects [4][5][6] and the remaining related to syndromic clefts. [7][8][9] A recent systematic literature review discussing the issue have also demonstrated that its incidence varies according to gender, 2:1 being the ratio of males to females for cleft lip and palate and 1:2 the approximate ratio of male to female for isolated CP, as well as unilateral clefts are more common than bilateral clefts, and of the unilateral cases of non-syndromic cleft lip and palate, left-sided cleft lips occur more frequently than right-sided cleft lips. 10 The multifactorial threshold model is one of the wellestablished models for describing the aetiology of CL/P.…”
Section: Introductionmentioning
confidence: 99%
“…A Net for data income from lying-in hospitals identified by ID codes (circles) sending data for at least 500 malformed infants (Split 500) to the coordination COORD (square). B Net for data income from lying-in hospitals identified by ID codes (circles) participating at 7 research projects (squares): HIPOSP: Hypospadias [6], PNF: natural family planning [23], DOWNSURV: Down syndrome survival [8], ECOTERAT: environmental teratogens [9], FOLAWARE: folic acid awareness [10], GLOBAL: global cleft project [11], and BINS: BINS development testing [12]. C Net for data outcome to scientific publications involving 12 centers from the Core Group identified by ID codes (squares), defined actors linked to most of the other actors, while the remaining centers belong to the periphery.…”
Section: Resultsmentioning
confidence: 99%
“…• GLOBAL (global cleft project): A cohort study of newborns with oral clefts to evaluate the impact of systematic pediatric care on morbidity and mortality at the age of 2 years [11]. …”
Section: Methodsmentioning
confidence: 99%